Investigation into the air treatment efficiency of biofilters of different structures - Baltrėnas, Pranas; Zagorskis, Alvydas (Journal of Environmental Engineering and Landscape Management, 2010)
Biological air treatment devices, biofilters, of four different structures with different origin charges, composed of natural zeolite granules, foam cubes and wood chips, were used for the experimental investigation. Biological and ad‐sorptive air treatment methods are employed to clean the air from volatile organic compounds by mixing foam and zeolite with wood chips. The use of complex cleaning technologies improves the efficiency of the device and extends the useful life of a charge. The investigation showed that microorganisms predominant in the process of biocleaning could also propagate in the charges of inorganic origin composed of natural zeolite. The dependences of biofilter treatment efficiency on the nature, concentration and filtration time of the fed pollutant were determined when cultivating associations of spontaneous microorganisms in a charge. The best filtration efficiency of the charge was achieved when acetone‐polluted air was fed into the device at a speed of 0.3 m/s. The treatment efficiency of a biofilter with a humidifying chamber reached 98% when cleaning the air from acetone with an initial concentration of the pollutant of 305 mg/m3. The cleaning efficiency of the device increases when reducing the concentrations of pollutants fed into the device and increasing the time of their filtration.Reikšminiai žodžiai: biofiltras, lakieji organiniai junginiai, biodegradacija, ceolitas, adsorbcija, mikroorganizmai.Santrauka. Eksperimentiniams tyrimams atlikti naudota keturi skirtingų konstrukcijų biologiniai oro valymo įrenginiai – biofiltrai su skirtingos kilmės įkrovomis, sudarytomis iš gamtines kilmes ceolito granulių, porolono kubelių bei medienos skiedrų. Poroloną ir ceolitą maišant su medienos skiedromis, lakiesiems organiniams junginiams iš oro valyti taikomi biologinis ir adsorbcinis oro valymo metodai. Įrenginio valymo efektyvumas pagerinamas bei įkrovos naudojimo trukmė ilgėja naudojant kompleksines valymo technologijas. Ištyrus nustatyta, kad biologinio valymo procese vyraujantys mikroorganizmai gali daugintis ir neorganinės kilmės įkrovose, sudarytose iš gamtinio ceolito. įkrovoje kultivuojant savaiminių mikroorganizmų asociacijas nustatytos biofiltru valymo efektyvumo priklausomybės nuo į įrenginį tiekiamo teršalo prigimties, koncentracijos, filtracijos laiko. Geriausiai įkrova filtravo 0,3 m/s greičiu į biofiltrą tiekiamą acetono garais užterštą orą. Šalinant iš oro acetoną, kai pradinė teršalo koncentracija 305 mg/m3, biofiltro su drekinimo kamera valymo efektyvumas siekė 98 %. Mažinant į biofiltrus tiekiamų teršalų koncentracijas bei didinant jų filtracijos laiką irenginių valymo efektyvumas didėja.Резюме. Для экспериментальных исследований использовались четыре устройства для биологической очистки воздуха – биофильтры разных конструкций. Загрузку биофильтров составляли гранулы естественного цеолита, поролон и древесина, которые использовались для очистки воздуха от летучих органических веществ. В случае применения для очистки воздуха поролона и цеолита в смеси с древесиной применялся биологический и адсорбционный методы. Применение комплексных технологий способствует улучшению эффективности очистки воздуха и продлению срока применения загрузки. Исследования показали, что в процессе биоочистки микроорганизмы могут размножаться и в неорганической загрузке, состоящей из природного цеолита. Культивируя в загрузке ассоциации микроорганизмов, найдены зависимости эффективности биофильтра от характера загрязнителя, его концентрации, времени фильтрации. Лучше всего загрузка фильтровала воздух, загрязненный парами ацетона и подаваемый в установку со скоростью 0,3 м/с. Эффективность очистки воздуха от ацетона при начальной концентрации загрязняющих веществ в 305 мг/м3 для биофильтра с камерой увлажнения составляла 98%. При снижении концентрации загрязняющих веществ, подаваемых в биофильтр, и повышении времени фильтрации загрязненного воздуха эффективность установки увеличивается.Ключевые слова: биофильтр, летучие органические вещества, биологический распад, цеолит, адсорбция, микроорганизмы.First Published Online: 14 Oct 2010